[Rezension von: Dietrich Christian Lammerts, Buddhist law in Burma] - Jákl, Jiří (Bijdragen tot de taal-, land- en volkenkunde, 2019)
"Buddhist Law in Burma: A History of Dhammasattha Texts and Jurisprudence, 1250–1850, by Lammerts, D. Christian" published on 12 Jul 2019 by Brill.